Prediction of human pharmacokinetics for low‐clearance compounds using pharmacokinetic data from chimeric mice with humanized livers - Kosuke Yoshida; Yuki Doi; Norihiko Iwazaki; Hidenori Yasuhara; Yuka Ikenaga; Hidetoshi Shimizu; Tomohisa Nakada; Tomoko Watanabe; Chise Tateno; Seigo Sanoh; Yaichiro Kotake (Wiley, 2022)
Abstract Development of low‐clearance (CL) compounds that are slowly metabolized is a major goal in the pharmaceutical industry. However, the pursuit of low intrinsic CL (CLint) often leads to significant challenges in evaluating the pharmacokinetics of such compounds. Although in vitro-in vivo extrapolation is widely used to predict human CL, its application has been limited for low‐CLint compounds because of the low turnover of parent compounds in metabolic stability assays. To address this issue, we focused on chimeric mice with humanized livers (PXB‐mice), which have been increasingly reported to accurately predict human CL in recent years. The predictive accuracy for nine low‐CLint compounds with no significant turnover in a human hepatocyte assay was investigated using PXB‐mouse methods, such as single‐species allometric scaling (PXB‐SSS) approach and a novel physiologically based scaling (PXB‐PBS) approach that assumes that the CLint per hepatocyte is equal between humans and PXB‐mice. The percentages of compounds with predicted CL within 2‐ and 3‐fold ranges of the observed CL for low‐CLint compounds were 89% and 100%, respectively, for both PXB‐SSS and PXB‐PBS approaches. Moreover, the predicted CL was mostly consistent among the methods. Conversely, the percentages of compounds with predicted CL within 2‐ and 3‐fold ranges of the observed CL for low‐CLint compounds were 50% and 63%, respectively, for multispecies allometric (MA) scaling. Overall, these PXB‐mouse methods were much more accurate than conventional MA scaling approaches, suggesting that PXB‐mice are useful tools for predicting the human CL of low‐CLint compounds that are slowly metabolized.